Studi komparatif disiplin kerja karyawan laki-laki dan perempuan pada Rumah Makan Sambal Lalap Jambi - Muttaqi, Ibror; Amin, Shofia; Kurniawan, Dwi (Jurnal Dinamika Manajemen, 2020)
This study aims to analyze the work discipline of employees at the Sambal Lalap Restaurant in Jambi City and to find out whether there are differences in work discipline based on gender characteristics. This thesis uses a descriptive approach by distributing questionnaires directly to respondents, namely employees of the Sambal Lalap Restaurant, Jambi City. The study results show that the Overall work discipline of Sambal Lalap Restaurant employees is considered high. Work discipline is as expected. From the research results, there are differences in the work discipline of employees. The work discipline of men is higher than the work discipline of female employees.